An empirical study on consumer automobile purchase intentions influenced by the COVID-19 outbreak. (October 2022) - Yan, Yingying; Zhong, Shiquan; Tian, Junfang; Jia, Ning
Abstract: The sudden onset of the coronavirus disease 2019 (COVID-19) may influence individuals' automobile purchase decisions, thus bringing great uncertainty to the automobile industry. To this end, the current study investigates individuals' behaviors regarding the purchase of automobiles, both before and after the outbreak of COVID-19. An ICLV (integrated choice and latent variable) model that integrates the socio-demographics, epidemic-related variables and psychological latent variables is applied. A survey of 960 respondents was conducted in China during the epidemic. The results suggest that there was an increase in the demand for automobiles after the COVID-19 outbreak. Firstly, demand was especially high in the groups of females, citizens, high-income earners, and people who own a driving license or who live in high epidemic risk areas. Secondly, although the severity of the epidemic for residences has a positive effect on automobile demand, travelers' perceived vulnerability is the key factor motivating purchases. Thirdly, the epidemic's negative income effects reduced the purchase propensity. Several dynamic policies are proposed to automobile consumption of the special time of the COVID-19 pandemic. Highlights: An ICLV model was applied to explore automobile purchase during the COVID-19. Regional variations of epidemic severity influenced automobile purchase decisions. Perceived vulnerability was the major motivation for the purchase of automobiles. The epidemic's negative income effects partially reduced the consumption propensity.